Quadrupole strength in isobaric triplets - Backes, B. C.; Dobaczewski, J.; Muir, D.; Nazarewicz, W.; Reinhard, Paul-Gerhard; Bentley, M. A.; Wadsworth, R. (Physical Review C, 2025)
The dependence of the E2 matrix elements on isospin projection Tz is linked to the conservation of the isospin symmetry. To study this conjecture, we calculated the B(E2:2+ → 0+) rates for the even-even T = 1 mirror nuclei with 42 ≼ A ≼ 98 within nuclear density functional theory, employing the generalized Bohr Hamiltonian, and carrying out angular momentum projection. We demonstrated that collective effects are crucial for describing experimental data near the N = Z line without invoking explicit beyond-Coulomb isospin symmetry-breaking corrections. We also determined the B(E2↓) values for odd-odd Tz = 0 nuclei 70Br and 78Y in doubly blocked configurations. We discussed the requirements for accurately describing isobaric analog states and emphasized how current theoretical results should be interpreted within the study of isospin symmetry across isospin triplets.
CRIS-Team Scopus Importer:2026-01-26